Preparation and Measurement of Controlled‐Release SO2 Fungicide Active Packaging at Room Temperature. (20th November 2012) - Xu, Wencai; Li, Dongli; Fu, Yabo; Wei, Hua
Abstract : In this work, we prepared a novel, three‐layer‐structure packaging film for keeping fruit fresh with a controllable‐release amount of SO2 fungicide. The outer layer was composed of biaxially oriented polypropylene film. The middle layer, prepared by mixing polyurethane adhesive with sodium metabisulfite and calcium sulfite powder, was the generating layer for the SO2 fungicide. The inner layer consisted of a blended film of ethylene vinyl acetate (EVA) and low‐density polyethylene. The water vapour transmission rate and oxygen transmission rate of the composite films, as well as the release amounts of SO2 in all sealed packaging bags, were measured. Next, the controllable‐release mechanism of SO2 fungicide was investigated, of which a preliminary discussion is included. The results of this experiment showed that the release amounts of SO2 in packaging bags were controlled by the additional amount of EVA resin contained in the inner layers. The more EVA resin added to the inner layer, the more SO2 fungicide was produced. Inside the packaging, SO2 was released continuously for approximately 50 days at room temperature (25º ± 1°C). SO2 concentrations ranged from 10 to 40 ppm in the freshness‐preserving packaging bags, effectively retarding mould growth and keeping the fruits fresh. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : A three‐layer‐structure packaging film with controllable‐release amount of SO2 fungicide was prepared for keeping fruit fresh. By modifying the proportion of ethylene vinyl acetate resin in ethylene vinyl acetate/low‐density polyethylene inner films, we obtained a series of adjustable films with different gas permeation rates, so intelligent control over the release amounts of SO2 in the range of 10‐40 ppm was possible. The gradual release of SO2 lasted more than 50 days at room temperature, making it effective for most fruit preservation.